Error Modeling based on Screw Theory and Sensibility Analysis of Reconfigurable Robot - Ge Weimin; Zhao Wen; Wang Xiaofeng; Liu Jun; Liu Zengchang (Jixie chuandong)
For the static error about dimensions error and geometric parameters error of reconfigurable robot caused by the design and manufacture of modules and its configuration change,the static geometric parameters error of reconfigurable robot is treated as the structural error and transmission error of the joint,and is assumed to be the result of tiny screw motion,then an kinematic error model of robotic is built by using the products of exponentials formula. Based on the relationship between input error and output error of reconfigurable robot,an error sensitivity coefficient model is established. The sensitivities coefficient of error parameters and the influence law of the error parameters on the position of the end-effector are analyzed with MATLAB,it is benefit to the further analysis and optimization of reconfigurable robot trajectory accuracy,and also provides effective theoretical foundation for designing and assembling of industrial robot with different accuracy requirements. A simulation experiment about a six-DOF（ degrees of freedom） reconfigurable robot is carried out,and the result show that the modeling method and sensitivity analysis method are effective and correct.